Impact of Knowledge Management on the Operational Risk of the Modern Organizations - Giedrė Gudauskienė; Asta Mikalauskienė (Vilnius University Open Series, 2022)
Organizations face a variety of challenges daily that sometimes make their operations risky. It is very important to define the risks and have a plan for managing threats. One way to manage risk is to use knowledge management. An organization is created by people, so maintaining for people is the most important goal of the organization. Brain drain can become significantly damage the organization. It is quite difficult to calculate the specific impact of risk on the organization in terms of qualitative indicators. However, it is unequivocally recognized that knowledge management in organizations is extremely important. Therefore, this topic – knowledge management in the risk management process of organizations - was chosen to find out how knowledge management, in addition to economic decisions, can contribute to an organization's risk aversion. This article aims to determine how the knowledge management process serves the operational risk management of organizations.